Recognizing Plastic Threats in Baggage X-Rays Using Deep Networks - Alawar, Mohammad Suhail Abdulwahid Abdulrahman (2019)
A Master of Science thesis in Electrical Engineering by Mohammad Suhail Abdulwahid Abdulrahman Alawar entitled, “Recognizing Plastic Threats in Baggage X-Rays Using Deep Networks”, submitted in December 2019. Thesis advisor is Dr. Usman Tariq and thesis co-advisors are Dr. Nasser Qaddoumi and Dr. Hasan Mir. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form).